Design and Analytical Study of Pavements Under Conformance Criteria - Manuka, Dagimwork Asele; Kuleno, Mengistu Mena (International Journal of Scientific Research in Civil Engineering, 2019)
Rapid development of motorization and urbanization has led for a need of rapid construction of road infrastructure. Better road demand and services requires cost effective and durable road construction materials. Flexible Pavement design mainly based on soil sub-grade strength and traffic loading. The design of rigid pavements uses equivalent standard axle load which doesn’t depend on the soil subgrade level. To provide better road, the quality needed, the factors which are extrinsic to the pavement and which have a significant effect on the required structure has been evaluated. Based on the evaluation of these extrinsic factors, the design thickness and intrinsic properties of the pavement structure has been ascertained so that the pavement exhibits desired level of performance over the life of the structure. The conformance criteria of pavement design is the standard of judgment used to evaluate the ability of the highway to serve and is the encompassing design factor which reflects the subjective desires of road users for a good pavement. Therefore, this study tried to compare a flexible and a rigid pavement alternate with different design life under conformance criteria of rigid pavement are described in thermal stress, traffic load, design life and modulus of subgrade reaction